The Effect of Capital Structure, Profitability, and Company Size on Stock Returns in the Energy Sector Listed on Bei for the 2019-2021 Period - Pratiwi, Nike Aditia; Dwiarti, Rina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this quantitative research is to examine the relationship between energy sector stock returns listed on the bei from 2019 to 2021 and factors such as capital structure, profitability, and firm size. For the years 2019–2021, a total of 150 energy-related enterprises listed on the IDX make up the study population. We used SPSS for statistical testing after collecting data from energy sector businesses' financial statements, which are available on the IDX website (www.idx.co.id). The findings demonstrated that stock returns are positively and significantly impacted by capital structure, profitability, and firm size, both alone and together.